2021
DOI: 10.1002/brb3.2228
|View full text |Cite
|
Sign up to set email alerts
|

Trend of recognizing depression symptoms and antidepressants use in newly diagnosed Parkinson's disease: Population‐based study

Abstract: Objectives: Although depression symptoms are common among patients with Parkinson's disease (PD), the medical literature still reports underrecognition of depression in patients with PD. Our main objective is to examine the trend of depression recognition during the first year of PD diagnosis using large population data. Methods:We conducted a population-based study of residents in Wales, using the Secure Anonymized Information Linkage (SAIL) Databank. We included newly diagnosed patients with PD aged 40 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…Importantly, depression is found at any stage of PD. Recently, data obtained in a large population indicated that 38% of patients are treated or diagnosed for depression within the year following diagnosis [30], consistent with other studies in de novo patients [8,31]. Depression is found in up to 70% of mid-to-advanced PD outpatients without dementia [4], and associated with other neuropsychiatric symptoms [32].…”
Section: Prevalencesupporting
confidence: 80%
See 2 more Smart Citations
“…Importantly, depression is found at any stage of PD. Recently, data obtained in a large population indicated that 38% of patients are treated or diagnosed for depression within the year following diagnosis [30], consistent with other studies in de novo patients [8,31]. Depression is found in up to 70% of mid-to-advanced PD outpatients without dementia [4], and associated with other neuropsychiatric symptoms [32].…”
Section: Prevalencesupporting
confidence: 80%
“…Moreover, depression may resolve over time in up to one-third of patients with PD, in line with a strong placebo effect in randomized clinical trials [240,241], where intensive medical follow-up and coping strategies may help, as observed for apathy [242]. Retrospective analysis of registry data shows that trend of diagnosis and treatment of depression in the first year following PD diagnosis slightly decreased from the years 2000 to 2015 [30]. Citalopram, amitriptyline, fluoxetine and mirtazapine were the most frequent pharmacological treatments used in recent years [30].…”
Section: Treatmentmentioning
confidence: 80%
See 1 more Smart Citation
“…DPD prevalence is higher than in the general population and may share pathophysiological mechanisms with other psychopathological symptoms (Laux 2022 ). In the last time, there is a slight decrease in depression, which could be due to an increase in depression recognition during the prodromal phase of PD (Orayj et al 2021 ). On the other hand, a higher prevalence of depression, anxiety, and worries in advanced PD has been observed during the COVID-19 pandemic (Montanaro et al 2022 ).…”
Section: Prevalence and Incidencementioning
confidence: 99%
“…Studies demonstrated that neurotoxin-induced PD models may exhibit depression-like behaviors, which sometimes manifest earlier than motor impairments (Mou et al 2022 ). However, due to an overlap with other symptoms primarily related to PD or side effects of medication, depression frequently remains unrecognized and undertreated (Laux 2022 ; Macías-García et al 2022 ; Orayj et al 2021 ; Politis et al 2010b ; Weintraub et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%